When do You Want It? Determinants of Future-Oriented Political Thinking - Rapeli, Lauri; Bäck, Maria; Jäske, Maija; Koskimaa, Vesa (Frontiers in Political Science, 2021)
Many studies have examined whether citizens prefer direct or stealth democracy, or participatory democratic processes. This study adds to the emerging literature that instead examines the temporal aspect of citizens’ process preferences. We use a survey with a probabilistic sample of the Finnish voting-age population (n= 1,906), which includes a measure of the extent to which citizens think democratic decision-making should maximize welfare today or ensure future well-being. Calling this dimension of democratic process preferences future-oriented political thinking (FPT), we demonstrate that people hold different but consistent views regarding the extent to which democratic politics should balance between present and future benefits. We find that FPT is linked to general time orientation, but the linkage varies across respondent groups. Politically sophisticated individuals are less future-oriented, suggesting that intense cognitive engagement with politics is linked with a focus on present-day politics rather than political investment in the future.